Transforming Sustainable Human Resource Development Management for Generation Z: Integrating Islamic Pedagogy and Vocational Skills: english - Waldan, Raziki; Zarkasi, Zarkasi; Hayatunnur Taqwa, Ria (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This study explores a sustainable human resource development management model for Generation Z by integrating Islamic pedagogy and vocational skills within the context of pesantren (Islamic boarding schools). The increasing demand for balancing spiritual and professional competencies in Islamic educational institutions necessitates structured management strategies. This research employs a qualitative approach using case studies and in-depth interviews with pesantren administrators and students. The findings reveal that structured curriculum design, digital-based training, and direct involvement in various professional sectors significantly enhance students' employability while maintaining their religious commitment. The integration of vocational training with Islamic education fosters holistic personal development, equipping students with the necessary competencies to navigate the modern workforce. This study contributes to the discourse on transformative Islamic education by demonstrating how structured management can effectively prepare Generation Z for both spiritual and professional success.